Relasi Habitus dalam Perikanan Napoleon Wrasse di Kabupaten Kepulauan Anambas, Kepulauan Riau - Siti Arieta (SIMULACRA: JURNAL SOSIOLOGI, 2019)
This study examines fishery management on Napoleon wrasse species in Anambas Islands district from a sociological point of view, using agent-structure relations perspective proposed by Pierre Bourdieu. It is found that the vital values of this species (ecological economic, and social) are not applied equally. Expansionist relationship within the use of this species had caused economic value is more prioritized than others.  As a result, sustainability of marine ecosystem becomes threatened. Other than that, fishing community as subsistence group is also ecologically in danger in a long term. Qualitative methodology was used for 8(eight) months period of time. This research was conducted at the center of Napoleon wrasse fishery within 3(three) sub districts consisting of 5(five) villages namely Air Sena (Siantan Tengah sub district), Batu belah (Siantan Timur sub district), also Putik, Ladan and Piabung (Palmatak sub district). Habitus formed by personal history and in addition to become a baseline for collective actions and commitment of involving actors has not been supporting the value of sustainable fisheries. This has caused incoherency between international and national commitment in protecting Napoleon wrasse.  Thus, this habitus within the fishing communities and the network of Napoleon wrasse fishery considered to be a fallacy of thinking. Therefore, a governance is urgently needed in order to add the value knowledge, to change desires and habits in terms of supporting the establishment of sustainable Napoleon wrasse fishery in Anambas Islands district.